Cystatin C-Based Equations Detect Hidden Kidney Disease and Poor Prognosis in Newly Diagnosed Patients with Multiple Myeloma - Francisco-Javier Cepeda-Piorno; Esther González-García; Alba Méndez-Gallego; Juan Torres-Varona; Vanesa García-Moreira; Christian Sordo-Bahamonde; Cristina AlberdiGarcía-del-Castillo; Elene Astobieta-Madariaga; Maria-Victoria Mateos-Manteca; Segundo González-Rodríguez (Advances in Hematology)
Objectives. The aim of this study was to compare the creatinine equations with cystatin C (CysC) equations to define renal impairment (RI) in newly diagnosed multiple myeloma (MM) patients and to analyse the equation that allows for identifying patients with more and worse prognostic factors. Methods. Renal function was evaluated prospectively in 61 patients with newly diagnosed untreated MM employing CKD-EPI and CAPA equations. The comparison was conducted using Bland–Altman graphics and Cohen’s Kappa statistic. Mann–Whitney T and Chi-square tests were used, and univariate and multivariate analyses were carried out. Results. According to the IMWG criteria, 26% of patients showed RI (3 women/13 men) whilst the use of CysC equations allowed us to identify up to 39% of patients (7 women/17 men). The CAPA equation was less biased and dispersed and more sensitive than CKD-EPI-creatinine. Furthermore, univariate analysis unveiled an association between decreased CKD-EPI-CysC and poor prognosis based on R-ISS-3. Conclusions. The IMWG criteria may underestimate kidney disease, mostly in women, which could affect the dose received as well as its toxicity. Altogether, our data suggest that equations that include CysC are more accurate to detect hidden kidney disease, as well as patients with more and worse prognostic factors, in newly diagnosed MM.